Identification of Chemical Compounds from Artemisia gmelinii using UPLC-QTOF-MS/MS and their Regulatory Effects on Immune Responses in DSS-Induced Colitis Mice - Son, Yang-Ju; Shin, Ji Min; Ha, In Jin; Erdenebileg, Saruul; Jung, Da Seul; Kim, Young Sik; Kim, Sang Min; Nho, Chu Won (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
Artemisia gmelinii Web. ex Stechm. (AG), a popular medicinal herb in Asia, has been used as a common food ingredient in Korea and is traditionally known for its anti-inflammatory properties. Therefore, in this study, we aimed to investigate whether AG relieves IBD, a classic chronic inflammatory disease of the gastrointestinal tract. We identified 35 chemical compounds in AG ethanol extract using ultra-high-performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry. In mice with DSS-induced IBD, AG administration attenuated the disease activity index and the serum and colonic levels of inflammatory cytokines and chemokines. AG treatment decreased nuclear factor-kappa B (NF-kappa B) signaling, a key mediator of inflammation, in the mouse colons. Additionally, AG extract enhanced immune responses in lymphoid tissues such as spleen and Peyer's patches. Thus, AG consumption potently ameliorated IBD symptoms and improved immune signaling in lymphoid tissues.
Keywords: NF-KAPPA-B; INFLAMMATORY-BOWEL-DISEASE; TRANSCRIPTION FACTOR; DENDRITIC CELLS; T-CELLS; IBD; SCOPOLETIN; SPLEEN; IL-10; PATHOGENESIS